PRODUCT QUALITY AND PRICE INFLUENCE ON CUSTOMER LOYALTY IN THE BUBBLE'KU BUBBLE DRINK AND ICE BLEND SOFT DRINK BUSINESS AT RAMAYANA DEPARTMENT STORE SUKABUMI CITY - Jaya, Umban Adi; Maryani; Salih, Martha Adi (Transpublika Publisher, 2022)
This study aims to determine the effect of product quality and price on customer loyalty either partially or simultaneously. The population in this study were all customers of Bubble'ku Bubble Drink and Ice Blend at Ramayana Department Store of Sukabumi City for June which as many as 900 people as the population. The sample of study was determined by Slovin formula, so that 90 sample was obtained. To test the analysis of research instruments, validity, reliability, and classical assumption tests were employed. For statistical analysis and relationship analysis, Pearson product moment correlation was used, as well as the coefficient of determination, multiple linear regression, and the t test and F test to test the null hypothesis. The findings reveal that simultaneously product quality and price significantly influence customer loyalty. By comparing Fstatistic with ttable (82.536 > 3.10), which means that H0 is rejected and H1 is accepted, and H0 is rejected and H2 is accepted, so the research hypotheses proposed in this study prove that product quality and price together (simultaneously) affect the customer loyalty. The contribution of product quality and price to customer loyalty is 65.5%, and the remaining 34.45% is influenced by variables not examined other than product quality and price. These variables include marketing strategy, location, promotion, marketing mix, service quality, promotion, and so on.